Antibiotics in surface water of East and Southeast Asian countries: A focused review on contamination status, pollution sources, potential risks, and future perspectives - Anh, Hoang Quoc; Le, Thi Phuong Quynh; Da Le, Nhu; Lu, Xi Xi; Duong, Thi Thuy; Garnier, Josette; Rochelle-Newall, Emma; Zhang, Shurong; Oh, Neung-Hwan; Oeurng, Chantha; Ekkawatpanit, Chaiwat; Nguyen, Tien Dat; et al. (The Science of the total environment, 2021)
This review provides focused insights into the contamination status, sources, and ecological risks associated with multiple classes of antibiotics in surface water from the East and Southeast Asia based on publications over the period 2007 to 2020. Antibiotics are ubiquitous in surface water of these countries with concentrations ranging from <1 ng/L to hundreds μg/L and median values from 10 to 100 ng/L. Wider ranges and higher maximum concentrations of certain antibiotics were found in surface water of the East Asian countries like China and South Korea than in the Southeast Asian nations. Environmental behavior and fate of antibiotics in surface water is discussed. The reviewed occurrence of antibiotics in their sources suggests that effluent from wastewater treatment plants, wastewater from aquaculture and livestock production activities, and untreated urban sewage are principal sources of antibiotics in surface water. Ecological risks associated with antibiotic residues were estimated for aquatic organisms and the prevalence of antibiotic resistance genes and antibiotic-resistant bacteria were reviewed. Such findings underline the need for synergistic efforts from scientists, engineers, policy makers, government managers, entrepreneurs, and communities to manage and reduce the burden of antibiotics and antibiotic resistance in water bodies of East and Southeast Asian countries. [Display omitted] •Antibiotic contamination status in East/Southeast Asia's surface water is reviewed.•Antibiotics are ubiquitous in surface water, especially in aquaculture and urban areas.•Antibiotic levels varied greatly from few ng/L to hundreds μg/L in surface water.•Ecological risks and prevalence of antibiotic resistance were widely observed.•Regional monitoring studies and environmental guidelines for antibiotics are needed.